2017
DOI: 10.1002/ppul.23694
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen screening and prognostic factors in children with severe ARDS of pulmonary origin

Abstract: BackgroundAcute respiratory distress syndrome (ARDS) is one of the most lethal diseases encountered in the pediatric intensive care unit (PICU). The etiological pathogens and prognostic factors of severe ARDS of pulmonary origin in children with respiratory virus infections were prospectively investigated.MethodsEnrolled children fulfilled the following criteria: (1) PICU admission; (2) age of 1 month to 16 years; (3) diagnosis of infectious pneumonia and respiratory virus infection; and (4) development of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
0
17
1
Order By: Relevance
“…It is characterized by inflammatory obstruction of the small airways and hyperinflation of the lungs and typically presents along with breathing problems and wheezing. RSV is the primary causative agent of bronchiolitis worldwide, causing between 70 or 80 percent of ARIs during the high season [18][19][20]. RSV was the only virus associated with bronchiolitis in this study.…”
Section: Discussionmentioning
confidence: 53%
“…It is characterized by inflammatory obstruction of the small airways and hyperinflation of the lungs and typically presents along with breathing problems and wheezing. RSV is the primary causative agent of bronchiolitis worldwide, causing between 70 or 80 percent of ARIs during the high season [18][19][20]. RSV was the only virus associated with bronchiolitis in this study.…”
Section: Discussionmentioning
confidence: 53%
“…Fungal infections are hardly ever the first pathogens Fig. 3 CT scan of the lung on day 12 after admission thought of, but fungal coinfections were described in children suffering ARDS due to viral infection [2]. Risk factors for fungal infections in ICU-patients are numerous, including immunosuppressive drugs and the differentiation of contamination or infection in nonhematological patients is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Polimicrobial infections are seen regularly in immunocompromised critically ill patients. Fungal coinfections were described in children [2] and adults suffering ARDS [3,4] due to viral infections. Pneumocystis jiroveci is often found in immunocompromised patients [5], as is the reactivation of Cytomegalovirus [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the serum levels of INF-γ and IL-6 also decreased after the administration of rTM. We previously reported that serum level of INF-γ on the intubation day was one of the possible prognostic factors affecting a fatal outcome in a child with severe ARDS of pulmonary origin [ 19 ]. On the basis of the previous results, poor outcome might be predicted in the present case.…”
Section: Discussionmentioning
confidence: 99%